2012
DOI: 10.3892/ijmm.2012.1068
|View full text |Cite
|
Sign up to set email alerts
|

Novel GATA6 loss-of-function mutation responsible for familial atrial fibrillation

Abstract: Atrial fibrillation (AF) is the most commonly sustained cardiac arrhythmia, and confers a substantially increased risk of morbidity and mortality. Increasing evidence has indicated that hereditary defects are implicated in AF. However, AF is genetically heterogeneous and the genetic etiology of AF in a significant portion of patients remains unclear. In this study, the entire coding sequence and splice junctions of the GATA6 gene, which encodes a zinc-finger transcription factor crucial for cardiogenesis, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 55 publications
(57 reference statements)
1
25
0
Order By: Relevance
“…Similarly, congenital cardiovascular malformations were previously confirmed in AF patients carrying GATA4, GATA5 or GATA6 mutations (49)(50)(51)(52)(53)(54)(55)(56)(57). Markedly, a long list of mutations in these genes has been implicated in a wide variety of congenital cardiovascular anomalies (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Similarly, congenital cardiovascular malformations were previously confirmed in AF patients carrying GATA4, GATA5 or GATA6 mutations (49)(50)(51)(52)(53)(54)(55)(56)(57). Markedly, a long list of mutations in these genes has been implicated in a wide variety of congenital cardiovascular anomalies (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75).…”
Section: Discussionmentioning
confidence: 83%
“…Developmental biology studies substantiate the key role for several transcription factors, including NKX2.5, GATA4, GATA5 and GATA6, in the normal cardiovascular morphogenesis (46)(47)(48), and multiple mutations in GATA4, GATA5 and GATA6 have been causally associated with AF (49)(50)(51)(52)(53)(54)(55)(56)(57). NKX2.5 is a member of the NK2-family of transcription factors and its expression and functions overlap with those of the GATA family during cardiovascular development, particularly in synergistic regulation of target gene expressions cooperatively with GATA4 (58), which justifies NKX2.5 as a prime candidate gene for AF.…”
Section: Introductionmentioning
confidence: 93%
“…Atrial fibrillation has been documented in some CHD patients harboring the germline mutations of GATA4, GATA5 and GATA6 (57)(58)(59)(60)(61)(62)(63)(64), which suggests that atrial fibrillation may share a common genetic origin with CHD. However, in the current investigation, no atrial fibrillation was documented in the 2 somatic GATA6 mutation carriers, which may be explained by insufficient electrocardiographic monitoring duration of only 24 h for paroxysmal AF, different genetic background, distinct mutational source, delayed or incomplete penetrance, epigenetic modifiers, or environmental factors (61).…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have identified novel mutations in GATA6 that co-segregated with AF and resulted in decreased transcriptional activity. 87,88 The LMNA gene encodes lamin A/C, an intermediate filament protein associated with the inner nuclear membrane. Mutations in this gene have been associated with many diseases such as dilated cardiomyopathy and muscular dystrophy.…”
Section: Non-ion Channel Mutationsmentioning
confidence: 99%